Financial markets in Central and Eastern Europe : stability and efficiency perspectives - Balling, Morten; Lierman, Frank, 1948-; Mullineux, A. W. (Routledge studies in the European economy, 2004)
This book charts the process of financial market reform in Central and Eastern Europe. Topics discussed will include the implications of future EU membership, and the strategies pursued by the World Bank and International Monetary Fund.